PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK FLUIDA STATIS KELAS X SEMESTER II DI SMA NEGERI 1 STABAT T.P. 2015/2016 - Hutahaean, Juniar; Lubis, Atikah Putri (Universitas Negeri Medan, 2016)
This study aims to determine the effect of Inquiry Training Model on learning outcomes of students in the subject matter of static fluid Class X SMA Negeri 1 Stabat 2nd semester 2015/2016 TP field. This research is quasi-experimental with Pretest-Postest Control Group Design. The study population were all students of class X of SMA Negeri 1 Stabat which consists of 10 classes with 335 students enrolled. Sample were taken from population which used cluster random sampling with 2 classes, class X2 as experimental class with 39 students enrolled and class X1 as control class with 38 students enrolled. Test instrument used is the achievement test which used to essay from 10 questions that have been validated and the observation sheets used to see the students learning activities which was observed by two observers and analyzed descriptively. The test Hypothesis used t test with . Based on the results shows the average value of the experimental class pretest = 21,47 with SD = 5,89 and control classes = 21,26 with SD = 5,84. At the prerequisite test showed that both groups of samples were normally distributed and homogeneous. The results of the pretest data analysis using t test showed that the abiliy of the students at the beginning of the second class of the same. The average value of the experi-mental class post-test =70,25 with SD= 9,63 and control classes = 61,68 with SD= 8,37. The results of post-test data analysis using t-test showed that obtained that there is the effect of Inquiry Training Model on learning outcomes of students in the subject matter of static fluid Class X SMA Negeri 1 Stabat 2nd semester 2015/2016 TP field. From the observation result of student learning activities of the first meeting until the meeting IV shows that the value average of Activities the students in the experimental class at 77.15 with the active category and the average value of the activities in the control class is 50.81 with active enough category.